Understanding sudden larch death – from epidemiology to host resistance - Dun, H (2021)
Phytophthora ramorum is responsible for disease outbreaks in a range of species, most prominently Sudden Oak Death in the USA and Sudden Larch Death in the UK. Our study focuses on the interactions between P. ramorum and two important forestry species in the UK, European larch (Larix decidua Mill.) (EL) and Japanese larch (Larix kaempferi (Lamb)Carr.) (JL). Larches are the third most important conifer species in the UK, with 126,000 hectares planted. By 2019 at least 20,700 hectares of larch had been killed due to P. ramorum infection or felled in efforts to contain the pathogen. Despite containment efforts, P. ramorum is expected to continue to spread and cause high levels of mortality in larch stands. Understanding the factors affecting spread, the response of larches to infection and the possibility of resistance to P. ramorum occurring within the larch population would help improve disease management.